Postcolonial Spaces
XVII, 208 p.
Keywords: With essays from a range of geographies and bringing together influential scholars across a range of disciplines, this book focuses on the role of space in the study of the politics of contemporary postcolonial experience, engaging with the spectrum of postcolonial spatialities which play a significant role in defining global postcolonial culture.